Effect of type of meat and storage on the quality of pre-cooked patties - REDDY, K PRABHAKAR; RAO, T S (The Indian Journal of Animal Sciences, 2013)
Patties were prepared by utilizing the meat from spent layers and ducks separately. The pre-cooked patties were stored at 5+-1Â° C for 6 days and evaluated for quality. Patties made with chicken meat had (P